Case Report: Factor VII Deficiency Presented With Cephalohematoma After Birth - Yuan-Chun Lo; Ching-Tien Peng; Ching-Tien Peng; Yin-Ting Chen (Frontiers Media S.A., 2021)
Introduction: Factor VII deficiency is a rare inherited autosomal recessive bleeding disorder with a global prevalence of 1/500,000. Most cases remain asymptomatic, and cases with severe clinical presentation are rarely reported.Case Presentation: A newborn male with no relevant maternal antenatal history, delivered via vacuum-assisted cesarean section, presented with a large cephalohematoma after delivery. Poor appetite, pale appearance, and bulging fontanelles were observed 2 days later, progressing to hypovolemic shock. Further imaging examination revealed a large intracranial hemorrhage. Serial laboratory examination revealed remarkable coagulopathy with prolonged prothrombin time and factor VII deficiency (<1%, severe type). The patient was genetically confirmed to have the FVII:c 681+1 G>T homozygous mutation. Brain hemorrhage was resolved with high-dose factor VII replacement therapy with recombinant activated factor VII. However, repeated hemothorax and intracranial hemorrhage were detected. Therefore, the patient was under regular factor VII supplementation with a rehabilitation program for cerebral palsy.Conclusions: A case of factor VII deficiency with large cephalohematoma and intracranial hemorrhage after birth is described herein, which was treated with high-dose replacement therapy. Variants of the FVII:c 681+1 G>T (IVS6+1G>T) homozygous genotype may present with a severe phenotype at the neonatal stage. We aim to share a unique neonatal presentation with a certain genotype and treatment experience with initial replacement therapy, followed by regular prophylactic dosage.